Uma contribuição à História das Mulheres nas Ciências no Brasil: Heloísa Alberto Torres, a primeira Diretora do Museu Nacional/UFRJ - Silva, Maria do Perpétuo Socorro Lopes de Sousa da (2018)
The issue of doing science for women in a markedly masculine world, behind the scenes scientific, and its trajectories built in an environment based on male values and standards, leads to an analysis of women's participation in the history of science in Brazil in the twentieth century. It uses as methodological input the qualitative approach with theoretical bibliographic and documentary procedures. Thus, the role of women in the struggle to be recognized independently of gender is highlighted, evidencing the work of the anthropologist Heloísa Alberto Torres (1895-1977) in the dissemination, promotion and dissemination of the sciences in Brazil through her work in the National Museum, consolidating the role of women in the history of science in Brazil and the renowned scientific institution that, throughout the 20th century, innovated by registering the participation of women in the promotion, dissemination and dissemination of science. Thus, we point out the first female director in the National Museum / UFRJ, naturalizing the science, pointing the place of women in society in the twentieth century, finally, stating that Brazilian female scientists are not lacking in the history of the sciences of the country. This period represented a new phase of existence of the Museum, having for the first time a woman as its director, which was an important milestone in demonstrating that the institutions began to grant spaces and possibilities for female scientists.